Asymmetry in infants' selective attention to facial features during visual processing of infant-directed speech - Smith, Nicholas A.; Gibilisco, Colleen R.; Meisinger, Rachel E.; Hankey, Maren (Frontiers in Psychology, 2013)
Two experiments used eye tracking to examine how infant and adult observers distribute their eye gaze on videos of a mother producing infant- and adult-directed speech. Both groups showed greater attention to the eyes than to the nose and mouth, as well as an asymmetrical focus on the talker’s right eye for infant-directed speech stimuli. Observers continued to look more at the talker’s apparent right eye when the video stimuli were mirror flipped, suggesting that the asymmetry reflects a perceptual processing bias rather than a stimulus artifact, which may be related to cerebral lateralization of emotion processing.